Evolution of aromatic structures during the reforming of bio-oil: Importance of the interactions among bio-oil components - Wang, Y.; Hu, Xun; Mourant, Daniel; Song, Yao; Zhang, L.; Lievens, Caroline; Xiang, J.; Li, Chun-Zhu (Elsevier Ltd, 2013)
Steam reforming of bio-oils is a viable way to produce syngas, but certain challenges need to be overcome before its commercial application. One of the main issues is the formation of tar and coke. Investigation of the evolution/formation of aromatic structures in steam reforming is an effective way to understand the mechanism of tar/coke formation. In this study, the pyrolysis, steam reforming and catalytic steam reforming of mallee wood bio-oil and its lignin-derived oligomers were conducted in a quartz reactor at various temperatures (500–850 °C). The product tars were characterised by ultraviolet (UV) fluorescence spectroscopy. The results indicate that the interactions among the compounds degraded from lignin and cellulose/hemicellulose obviously affect the evolution of aromatic structures during the catalytic steam reforming of bio-oil. Furthermore, Raman spectroscopy of the catalyst provided information on the interactions of the volatile compounds and the deposit on the catalysts.